ANALISA PENGARUH RETURN ON EQUITY, EARNING PER SHARE, DAN DEBT TO EQUITY RATIO TERHADAP STOCK PRICE LEVEL PADA PERBANKAN SYARIAH INDONESIA - Mukhlisul Muzahid; Aryati Aryati; Siti Permata Hadi (Politeknik Negeri Lhokseumawe, 2022)
Abstract : This study aims to determine the effect of Return On Equity, Earning Per Share, and Debt To Equity Ratio on the level of stock prices. This research was conducted on Islamic banking companies on the Indonesia Stock Exchange. The data used in this study is monthly data for the period May 2018 to 2020 obtained based on the publication of the Indonesia Stock Exchange. The population in this study are companies that are members of Islamic Commercial Banks as many as 14 companies. The sample of this research was obtained as many as 3 sample companies using purposive sampling method. Data analysis was performed using multiple linear regression analysis techniques with the help of SPSS v.18 software. The results of the study simultaneously show that Return On Equity, Earning Per Share, and Debt To Equity Ratio have a significant effect on the level of stock prices. Partially Return On Equity has a positive and significant effect on the level of stock prices, Earning Per Share has a positive and significant effect on the level of stock prices, and the Debt to Equity Ratio has no effect on the level of stock prices.Keywords : Return On Equity, Earning Per Share, Debt to Equity Ratio, Stock Price Level